2020
DOI: 10.1155/2020/2368164
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of First-Line Immunotherapy in Combination with Chemotherapy for Patients with Extensive-Stage Small Cell Lung Cancer: A Systematic Review and Network Meta-Analysis

Abstract: Background. The prognosis of patients with extensive-stage small cell lung cancer (SCLC) is poor. Adding an immune checkpoint inhibitor (ICI) to chemotherapy may exert a synergistic effect and improve survival outcomes. However, for treatment-naive extensive-stage SCLC patients, the efficacy of immunotherapy in combination with cytotoxic chemotherapy remains controversial. Objective. To evaluate the benefits and risks of the combination of immunotherapy and chemotherapy and to assess the comparative effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 33 publications
3
16
0
Order By: Relevance
“…In addition, these two PD-L1 inhibitors plus chemotherapy have been approved by FDA as first-line therapy for ES-SCLC ( Table 1). Recently, several meta-analyses analyzed different firstline treatments for ES-SCLC patients and demonstrated that PD-L1 inhibitors durvalumab and atezolizumab plus etoposide-based chemotherapy may be the best choice as first-line therapy for ES-SCLC patients (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these two PD-L1 inhibitors plus chemotherapy have been approved by FDA as first-line therapy for ES-SCLC ( Table 1). Recently, several meta-analyses analyzed different firstline treatments for ES-SCLC patients and demonstrated that PD-L1 inhibitors durvalumab and atezolizumab plus etoposide-based chemotherapy may be the best choice as first-line therapy for ES-SCLC patients (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Small cell lung cancer (SCLC) is a deadly disease that represents about 15% of all lung cancers [ 1 ]. It is clinically characterized by a rapid growth and early metastatic widespread, around 70% of cases present with extensive-stage SCLC(ES-SCLC) at diagnosis [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous meta-analyses comparing ICIs plus chemotherapy with chemotherapy alone [ 45 , 46 ], and others comparing treatment regimens for previously untreated ES-SCLC [ 47 , 48 , 49 ] have reported that the ICIs+chemotherapy group had a better efficacy profile than the chemotherapy alone group. However, to date, no study has compared OS and PFS across six therapeutic regimens, including Pem+EP, Dur+EP, Atz+EP, AP, IP, and EP, for previously untreated ES-SCLC.…”
Section: Discussionmentioning
confidence: 99%